Politics of honor in Ottoman Anatolia sexual violence and socio-legal surveillance in the eighteenth century - Tuğ, Başak (Ottoman empire and its heritage)
In Politics of Honor, Basak Tug examines moral and gender order through the glance of legal litigations and petitions in mid-eighteenth century Anatolia. By juxtaposing the Anatolian petitionary registers, subjects' petitions, and Ankara and Bursa court records, she analyzes the institutional framework of legal scrutiny of sexual order. Through a revisionist interpretation, Tug demonstrates that a more bureaucratized system of petitioning, a farther hierarchically organized judicial review mechanism, and a more centrally organized penal system of the mid-eighteenth century reinforced the existing mechanisms of social surveillance by the community and the co-existing "discretionary authority" of the Ottoman state over sexual crimes to overcome imperial anxieties about provincial "disorder".